PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN PADA WARUNG MINA CABANG DALUNG - I Gusti Ayu Agung Maharani; Ni Putu Nita Anggraini; Pande Ketut Ribek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The development of the culinary business world is growing in line with the development of the era of globalization, this is marked by the high level of business competition becoming a challenge for business people in marketing the products they offer to meet the needs and desires of consumers. The purpose of this study was to determine the effect of product quality, service quality and price perception on consumer satisfaction at Warung Mina Branch Dalung. This research was conducted at Warung Mina Branch Dalung which is located on Jl. Raya Padang Luwih No. 118, Dalung district. North Kuta, with the object of research is product quality, service quality, price perception and customer satisfaction at Warung Mina Branch Dalung. The population in this study is the consumers of Warung Mina Branch of Dalung whose number is not known with certainty. The sample of this study was determined by accidental sampling method and calculated using the Lemeshow formula, so that the number of samples was 100 people. The data analysis technique used is many linear regression analysis. The test results show that product quality, service quality and price perception have a positive and significant effect on consumer satisfaction at Warung Mina Branch Dalung. In this study, the price perception variable is the most dominant variable affecting consumer satisfaction.